PENGEMBANGAN MATERI TIPE KEPRIBADIAN MENURUT HANS J. EYSENCK UNTUK SISWA SMA/SEDERAJAT - Rasyidah, Nur; Yakub, Elni; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :One of the efforts that individual is able to practice and identifythemselves with all the existing potential so that they can take necessary action for selfimprovement and their position in the surrounding environment is by studying thepersonality and also learn about the various types of human personality.Therefore, researcher found it necessary to develop a material about Personality Typeby Hans J. Eysenck which is expected to be used by teacher's guidance andcounselling to be teached to their students. This material was compiled using themethod of Research and Development (R&D). The purpose of this research is 1)Compile the material about Personality Type by Hans J. Eysenck in terms of clarity,systematics, images, games, videos, latest and completeness of material. 2) To findout about result quality of the material that have been produce before. This materialis validated by supervising lecturer 1& 2, teacher of guidance and counseling and38 Students SMA Negeri 2 Pekanbaru. This material are teached to the students in 4 x45 minutes of study time. This material consist of definition of personality by Hans J.Eysenck, classification of personality types by Eysenck, difference traits, attitudes andactions, social interaction, internet usage, social network, also individual learningstyles of extrovert and introvert types. The result of this material development shows thequality of material produced is in a “Very Good” category, with acquisition of ascore is 4,4 for all aspects of research assessment.Keywords: Personality Type by Hans J. Eysenck, extrovert and introvert types